Setting the Agenda for Further District Heating Reform in Ukraine - World Bank (World Bank, Washington, DC, 2020)
Since 2015, Ukraine has taken major legislative and policy steps to reform its energy sector and introduce competition for natural gas and electricity services, in particular by establishing cost-reflective pricing, phasing out implicit tariff subsidies, and introducing the ability for consumers to change suppliers. Because of this transition towards market-based arrangements, the Ukrainian district heating (DH) sector has been faced with major technical, commercial, financial, operational, and institutional challenges. The main purpose of this report is to present an analysis of the status of DH sector reform and of the remaining challenges, and to identify proposals to address these challenges, so as to facilitate the emergence of a comprehensive DH sector reform agenda, including an alignment of key decision-makers and stakeholders around crucial reform components and a process to implement these reforms. The report is organized as follows: section one gives introduction. Section two provides an overview of the current situation of the DH sector including its relative weight in the country’s energy consumption in the heating services provided to the population, its financial situation, and the estimate of investments at the national level needed for modernization of the DH infrastructure. Section three analyzes the reform actions impacting the DH sector which have been implemented or initiated over the last few years, presenting the achievements as well as the limitations of these reforms. The outstanding key issues to be addressed as part of DH sector reform are analyzed in section four. Section five discusses two reform options for the DH sector which have been discussed among stakeholders for some time but for which there is no consensus. Section six identifies a list of reform actions for each major sector reform strategic priority, separating short term actions, and medium-term actions to be implemented in 2020 as part of a comprehensive package of reforms after adequate technical preparation and consultations.